Organic Matter Processing on Dry Riverbeds is More Reactive to Water Diversion and Pollution Than on Wet Channels - Pérez-Calpe, Ana Victoria; de Guzman, Ioar; Larrañaga, Aitor; von Schiller, Daniel; Elosegi, Arturo (Frontiers in Environmental Science, 2022)
Rivers are severely affected by human activities and many are simultaneously impacted by multiple stressors. Water diversion for hydropower generation affects ecosystem functioning of the bypassed reaches, which can alternate between periods with natural discharge and others with reduced flow that increase the surface of dry riverbeds. In parallel, urban pollution contributes a complex mixture of nutrients, organic matter, heavy metals, pesticides and drugs, thus becoming an important stressor in rivers. However, there is little information on the interaction between both stressors on ecosystem functioning, and particularly on organic matter processing, a key process linked to the input of energy to food webs. To assess the impact of water diversion and urban pollution on organic matter processing, we selected four rivers in a pollution gradient with a similar diversion scheme and compared reaches upstream and downstream from the diversion weirs. We measured leaf-litter decomposition and carbon dioxide (CO2) fluxes in both the wet channel and the dry riverbed. Water diversion and pollution in the wet channel did not affect CO2 fluxes, but reduced microbial decomposition, whereas in the dry riverbed, their interaction reduced total and microbial decomposition and CO2 fluxes. Thus, both stressors affected organic matter processing stronger in dry riverbeds than in the wet channel. These results show that dry riverbeds must be taken into account to assess and manage the impacts of human activities on river ecosystems.